PENGARUH SOSIALISASI PAJAK, PEMAAHAMAN PERPAJAKAN, DAN TINGKAT PENDIDIKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI PROVINSI LAMPUNG - liani pitaloka; Endang Asliana; Irawan (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2022)
This study aims to determine the effect of tax socialization, tax understanding, and education level on MSME taxpayer compliance in Lampung Province. The population in this study is MSME taxpayers registered at the Lampung Province Tax Service Office as many as 126 MSME taxpayers. Sampling using Proportional Random Sampling technique. This technique is used because the population has members/elements that are not homogeneous and proportionally stratified. The data collection method used a questionnaire distributed online using google forms and documentation. The analytical tool used is multiple linear regression with the hypothesis test, namely the t-test performed using the SPSS.V.22 program. The results showed that tax socialization had a significant positive effect on MSME taxpayer compliance in Lampung Province, understanding of taxation had a significant positive effect on MSME taxpayer compliance in Lampung Province, while education level had no effect on MSME taxpayer compliance in Lampung Province